Connections between the completion of normed spaces over non-archimedean fields and the stability of the Cauchy equation - Schwaiger, Jens (Annales Mathematicae Silesianae, 2020)
In [12] a close connection between stability results for the Cauchy equation and the completion of a normed space over the rationals endowed with the usual absolute value has been investigated. Here similar results are presented when the valuation of the rationals is a p-adic valuation. Moreover a result by Zygfryd Kominek ([5]) on the stability of the Pexider equation is formulated and proved in the context of Banach spaces over the field of p-adic numbers.